RADA VARGA, CARVING A PROFESSIONAL IDENTITY. THE OCCUPATIONAL EPIGRAPHY OF THE LATIN WEST, ARCHAEOPRESS ROMAN ARCHAEOLOGY 73, OXFORD, ARCHAEOPRESS, 2021, 119 P., ISBN 9781789694642 - Annamaria Izabella Pazsint (Journal of Ancient History and Archaeology)
Rada Varga, Carving a Professional Identity. The occupational epigraphy of the Latin West, Archaeopress Roman Archaeology 73, Oxford, Archaeopress, 2021, 119 p., ISBN 9781789694642